EVALUASI PROGRAM GERAKAN MENABUNG DI SDN 23 MENDO BARAT DENGAN MODEL STAKE - Aldri, Amar; Rahmatullah, Rofika; Asyraf Suryadin; Siti Aisyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This evaluation was conducted to assess the Savings Movement program at SDN 23 Mendo Barat using the Stake model. The main focus of the evaluation was how this program was able to develop a habit of saving in elementary school students. Problems that emerged in the field included low student motivation to set aside money regularly, the perception that money was only for snacks, and a lack of guidance from parents and teachers regarding the importance of saving from an early age. The evaluation used a qualitative approach with the Stake method. Data were collected through interviews, observations, and document analysis involving students, teachers, and parents. The evaluation results showed that the program was running quite well with the support of the school, teachers, and parents. Regular saving activities not only trained discipline but also fostered a sense of responsibility and appreciation for the value of money. Obstacles identified were uneven student motivation, limited parental involvement, and manual savings record keeping. Nevertheless, this program was quite effective in developing savings habits and supporting children's financial literacy. This evaluation recommended that the school strengthen cooperation with parents and develop a more practical record- keeping system.